Can Podocalyxin Immunoreactivity Facilitate Histopathological Diagnosis of Placenta Accreta Spectrum (PAS) Disorders? - Sayit, Bahar; Atilgan, Remzi; Aslan, Melike; Kuloglu, Tuncay; Ozercan, I. Hanifi; Hancer, Serhat; Tepe, Batuhan (Wiley, 2026)
Aim: Placenta accreta spectrum (PAS) is linked to severe maternal morbidity and mortality, ranging from severe bleeding to death from placental failure at birth. PAS arises when the placenta invades the myometrium abnormally rather than the decidua basalis. Although uterine scarring is known to play a part in the pathophysiology of PAS, the fact that it can be observed in women who are nulliparous or who have not had uterine surgery raises the possibility that immunohistological changes may also play a role in the development of PAS in addition to anatomical defects. Ki-67 and vascular endothelial growth factor (VEGF) are crucial for placental angiogenesis and trophoblast invasion. The migration and invasion of cancer cells are especially aided by podocalyxin (PCX) overexpression. In this study, we want to examine PCX immunoreactivity in pathology samples from patients with a placenta increta diagnosis. Methods: We compared the hysterectomy specimens of two groups of patients: those who had a cesarean hysterectomy with a clinical diagnosis of placenta increta, and those who had histopathologically confirmed placenta increta but were not diagnosed with placenta increta. Results: We demonstrated that patients with placenta increta had considerably higher levels of VEGF, Ki-67, and PCX immunoreactivity. Conclusions: In PAS cases undergoing clinical hysterectomy, the increase in PCX immunoreactivity can be used as an immunohistochemical marker to support the diagnosis of PAS in histopathological confirmation of PAS diagnosis.
Keywords: biomarker; Ki-67; placenta accreta spectrum; placenta increta; podocalyxin; VEGF